2023
DOI: 10.1186/s12889-023-16017-8
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and enablers to testing for hepatitis C virus infection in people who inject drugs – a scoping review of the qualitative evidence

Abstract: Background Injection drug use is the primary mode of transmission of hepatitis C virus (HCV) infection in the developed world and guidelines recommend screening individuals with current or history of injection drug use for HCV; however, the majority of those living with HCV in Canada are not aware of their positive status. This low level of HCV status awareness suggests that screening is not effective with current testing strategies. The aim of this review is to determine what barriers and enab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…HCV testing rates were lower than HIV testing rates. This may be because clinicians and patients view HCV as a chronic disease that is common in PWUD and not an urgent issue, because PWUD feel they are at low risk, or because providers incorrectly believe HCV treatment should only be offered after a period of abstinence from drug use [ 52 ]. Thus, patients admitted with complications of active substance use may not fall within clinicians’ routine practice for HCV testing and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…HCV testing rates were lower than HIV testing rates. This may be because clinicians and patients view HCV as a chronic disease that is common in PWUD and not an urgent issue, because PWUD feel they are at low risk, or because providers incorrectly believe HCV treatment should only be offered after a period of abstinence from drug use [ 52 ]. Thus, patients admitted with complications of active substance use may not fall within clinicians’ routine practice for HCV testing and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It is also encouraging that many participants in our study agreed that HCV treatment is warranted even if symptoms are not present, and that treatment of HCV will keep infected people healthier longer. Previous work has suggested that low perceived benefit of treatment and competing priorities (such as need for food or safe shelter) are significant barriers to seeking HCV testing or treatment (Balsom et al, 2023 ; Nápoles et al, 2019 ). However, those who completed the survey in our study had already indicated a desire for testing and care navigation services, so the opinions expressed in our survey may not represent the opinions of the larger probation population.…”
Section: Discussionmentioning
confidence: 99%